Effect of Telemonitoring and Nurse-Led Collaboration on Self-Management and Quality of Life in Heart Failure Patients in West Java - Lindayani, Linlin; Nurdina, Gina; Anggraini, Dian; Herdiman, Herdiman; Darmawati, Irma; Mutiar, Astri (STIKep PPNI Jawa Barat, 2025)
Aims: This study aimed to assess the combined effects of telemonitoring and nurse-led collaborative care on self-management, medication adherence, QoL, and hospital readmission rates among HF patients in West Java, Indonesia. Methods: A randomized controlled trial (RCT) was conducted with 120 HF patients randomized into an intervention group (telemonitoring and nurse-led collaborative care) and a control group (standard education). The intervention included health education, telemonitoring of clinical parameters, and regular nurse follow-ups. The primary and secondary outcomes—hospital readmissions, self-management, medication adherence, and QoL—were measured using validated instruments. Data analysis was performed using multivariate regression and chi-square tests. Results: Participants in the intervention group demonstrated significant improvements in self-management (mean score increased from 62.4 to 78.3), medication adherence (mean core increased from 4.3 to 6.8), and QoL (mean score decreased from 51.8 to 38.4) compared to the control group (p < 0.001). Additionally, the 180-day hospital readmission rate was significantly lower in the intervention group (30.0%) compared to the control group (60.0%, p < 0.001). Telemonitoring and nurse-led care independently reduced the odds of readmission by 3.8 times (OR: 3.8, 95% CI: 1.9–7.4, p < 0.001). Conclusion: This scalable and effective model for HF management highlights the importance of culturally tailored interventions in low- and middle-income countries, offering a practical approach to overcoming resource limitations.